Purification and characterization of mouse bispecific monoclonal antibodies recognizing carcinoembryonic antigen (CEA) and doxorubicin - Osborne, Perry Alonzo, 1968- (1996)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1996. Medicine Bibliography: leaves 163-173. In Process